A Comparison of Re-arrest Outcomes Between Youth in Juvenile Drug Court, Teen Court, Probation, and Dismissed Cases - Hartsell, Elizabeth N. (Crime & delinquency, 2022)
This study identified populations served by diversion and explored potential effects of diversion by comparing re-arrest among diverted youth, youth on probation, and youth whose case were dismissed using a large sample of low-risk youth in Florida. Using propensity score estimation, results found youth who participated in teen court or drug court or who were on probation were more likely to be re-arrested within 1 year compared to youth whose case was dismissed. Juvenile drug court participants were more likely to be re-arrested than teen court participants. Youth on probation were more likely to be re-arrested compared to teen court participants, but there was no significant difference in re-arrest between youth on probation and juvenile drug court participants.